Magma source feature and eruption age of volcanic rocks in the Tram Tau district, Tu Le Basin - Hoang*, Nguyen; Huong, Tran Thi; Bac, Dao Thai; Vu, Nguyen Van; Thu, Nguyen Thi; Thang, Cu Sy; Dang, Pham Thanh (Vietnam Journal of Earth Sciences, 2016)
A set of samples including porphyritic rhyolite, rhyo-trachyte, trachyte and basalt was collected in the Tram Tau district, Tu Le Mesozoic Basin, in NW Viet Nam for analysis for major, trace, elemental and Rb-Sr and Sm-Nd isotopic compositions. The volcanic rocks are alkaline and highly enriched in trace elements including rare earth elements (REEs). However, primitive mantle and chondrite trace element normalized patterns expose strong negative anomalies for Ba, Sr, Eu and Ti, possibly reflecting fractional crystallization of plagioclase (for Sr and Eu), pyroxene, and especially amphibole (for Ba and Ti). The measured 87Sr/86Sr isotopic ratios, varying between 0.8142 and 0.75283, are plotted against the corresponding 87Rb/86Sr forming an isochron that provides an age of 157± 2.9 Ma with an initial 87Sr/86Sr ratio of 0.708, corresponding to late Jurassic - early Cretaceous (J3-K1) in agreement with previously reported data. The corresponding Nd isotopic compositions expressed as eNd (157Ma) vary from -8,27 to -2.32 and the Nd model ages are Mesoproterozoic, ranging from 1 to 1.3 Ga. This highly enriched magma was postulated to have formed by mixing of a depleted mantle and Mesoproterozoic crustal rocks (for example, granite) following a continental extension event. Mixing between crustal rocks having strontium isotopic ratios of 0.715 and 0.730 and a depleted mantle with 87Sr/86Sr ratio of 0.703 would occur, respectively, at 3÷4% and 2÷5% to generate the observed strontium isotopic ratios in the Tram Tau volcanic rocks. References Anders, E., Grevesse, N., 1989. Abundances of the elements: meteorite and solar. Geochim. Cosmochim. Acta 53, 197-214. Chung, S.L., Jahn, B.M., 1995. Plume-lithospheric interaction in generation of the Emeishan flood basalts at the Permian-Triassic boundary. Geology 23(10), 889-892. Chung, S.L., Lan, C.-Y., Lo, C.H., Lee, T.Y., Wang, P.-L., Hoa, T.T., Thanh, H.H., Anh, T.T., 1998. The Indosinian orogeny and closure of eastern Paleo-Tethys: Amalgamation between the Indochina and South China blocks in the early Triassic. GEOSEA 98, 17-19. Chung, S.L., Lee, T.Y., Lo, C.H., Wang, P.L., Chen, C.Y., Nguyen, T.Y., Tran, T.H., Wu, G.Y., 1997. Intraplate extension prior to continental extrusion along the Ailao Shan-Red River shear zone. Geology 25, 311-314. Cung Thuong Chi, Dorobek, S.L., 2004. Cretaceous palaeomagnetism of Indochina and surrounding regions: Cenozoic tectonic implications. In: Malpas, J., Fletcher, C.J.N., Ali, J.R., Aitchison, J.C. (Eds.), Aspects of the Tectonic Evolution of China, 226. Geological Society Special Publication, 273-287. Cung Thuong Chi, Geissman, J., 2013. A review of the paleomagnetic data from Cretaceous to lower Tertiary rocks from Vietnam, Indochina and South China, and their implications for Cenozoic tectonism in Vietnam and adjacent areas. Journal of Geodynamics, 69, 54-64. Dovjikov, A.E. (Editor), 1965. Geology of Northern Viet Nam. General Dept. Geology of Viet Nam. Science and Technique Publishing, Hanoi, 668 (in Russian). Flower, M.F.J., Russo, R.M., Tamaki, K., Hoang, N., 2001. Mantle contamination and the Izu-Bonin-Mariana (IBM) ’high-tide mark’: evidence for mantle extrusion caused by Tethyan closure. Tectonophysics, 333, 9-34. Flower, M.F.J., Tamaki, K., Hoang, N., 1998. Mantle extrusion: a model for dispersed volcanism and DUPAL-like asthenosphere in East Asia and the WPAC. In: Flower, M.F.J., Chung, S.L., Lo, C.H. (Eds.), Mantle Dynamics and Plate Interactions in east Asia, Geodynamics Series, vol.27. American Geophysical Union, 67-88. Gilder, S.A., Gill, J., Coe, R.S., Zhao, X.X., Liu, Z.W., Wang, G.X., Yuan, K.R., Liu, W.L., Kuang, G.D., Wu, H.R., 1996. Isotopic and paleomagnetic constraints on the Mesozoic tectonic evolution of south China. Journal of Geophysical Research 101(16), 137-16, 154. Hutchison, C., 1989. Geological Evolution of south-East Asia. Clarendon Press, Oxford, 368. Ionov, D., Hofmann, A.W., 1995. Nb-Ta-rich mantle amphiboles and micas: Implications for subduction-related metasomatic trace element fractionations. Earth Planet. Sci. Lett. 131, 341-356. Ishizuka, O., Taylor, R.N., Milton, J.A., Nesbitt, R.W., 2003. Fluid-mantle interaction in an intra-oceanic arc: constraints from high-precision Pb isotopes. Earth and Planetary Science Letters 211, 221-236. Jahn, B.M., Zhou, X.H., Li, J.L., 1990. Formation and tectonic evolution of southeastern China and Taiwan: isotopic and geochemical constraints. Tectonophysics 183, 145-160. Lan, C-Y., Chung, S-L., Shen, J.J-S., Lo, C-H., Wang, P-L., Hoa, T.T., Thanh, H.H., Martzman, S.A., 2000. Geochemical and Sr-Nd isotopic characteristics of granitic rocks from northern Vietnam. Journal of Asian Earth Sciences 18, 267-280. Le Bas, M.J., Le Maitre, R.W., Streckeisen, A., Zanettin, B., 1986. A chemical classification of volcanic rocks based on the total alkali-silica diagram. Journal of Petrology 27, 745-750. Leloup, P.H., Lacassin, R., Tapponnier, P., Schärer, U., Zhong, D.L., Liu, X.H., Zhang, L.S., Ji, S.C., Phan Truong, T., 1995. The Ailao Shan-Red River shear zone (Yunnan, China), Tertiary transform boundary of Indochina. Tectonophysics 251, 3-84. Ludwig, K.R., 2012. Isoplot, a geochronological toolkit for Microsoft Excel. Berkeley Geochronology Center, Special Publication, 5, 75. Nguyen Dac Dong (Editor), 2000. Reports on ‘geological mapping and mineral resource exploration of the Tram Tau sheet, 1:50,000 scale’. Archives of Geology, General Dept. Geology and Minerals of Viet Nam, Hanoi (in Vietnamese). Nguyen Dinh Hop (Editor), 1997. Reports of geological mapping (1:50,000) of the north Tu Le - Van Ban sheet. Archives of Geology, General Dept. Geology and Minerals of Viet Nam, Hanoi (in Vietnamese). Nguyen Hoang, Flower, M.F.J., Carlson, R.W., 1996. Major, trace element, and isotopic compositions of Vietnamese basalts: interaction of hydrous EM1-rich asthenosphere with thinned Eurasian lithosphere. Geochimica et Cosmochimica Acta 60, 4329-4351. Nguyen Hoang, Flower, M.F.J., Cung Thuong Chi, Pham Tich Xuan, Hoang Van Quy, Tran Thanh Son, 2013. Collision-induced eruptions at Pleiku and Buon Me Thuot, south-central Viet Nam. Journal of Geodynamics 69, 65-83. Nguyen Hoang, Itoh, J., Miyagi, I., 2011. Subduction components in Pleistocene to recent Kurile arc magmas in NE Hokkaido, Japan. Journal of Volcanology and Geothermal Research 200, 255-266. Nguyen Hoang, Nguyen Dac Lu, Nguyen Van Can, 2004. Paleozoic volcanic rocks in the Song Da region: mantle sources and dynamics. J. Geology 282 (7-8, Series A), 10-18 (in Vietnamese with English abstract). Nguyen Hoang, Uto, K., 2006. Upper mantle isotopic components beneath the Ryukyu arc system: evidence for ‘back-arc’ entrapment of Pacific MORB mantle. Earth and Planetary Science Letters 249, 229-240. Nguyen Trung Chi, Bui Minh Tam, Phan Truong Thi, 1995. Geochemistry of the magmatism rocks from Tu Le zone, northwest Vietnam and their tectonic signification on Cenozoic evolution. Vietnam National University (Hanoi)-University Paris VI Workshop “Cenozoic Evolution of Indochina Peninsula” Abstracts, 75-76. Nguyen Truong Giang, Nguyen Dac Dong, Nguyen Quang Hung, Tran Thanh Hai, Dang Tran Huyen, Pham Nguyen Phuong, 2003. New discoveries and characteristics of sediment - volcanic rocks in the Tram Tau area, Tu Le zone, Yen Bai province. Geology and Mineral Resources, 8, 93-104 (in Vietnamese with English abstract). Nguyen Van Nhan, Hoang Minh Thao, 2002. Geochemical characteristics of Pb-Zn mineralization in the Tu Le area. Journal of Geology, A(271), 7-8 (in Vietnamese with English abstract). Nguyen Van The, 1999. Report on geology and mineral resources and accompanying geological map of 1:50,000 scale. Archives of Geology, General Dept. Geology and Minerals of Viet Nam, Hanoi. Nguyen Vinh (Editor), 2005. Geology and Mineral Resources of the Yen Bai sheet (1:200,000 scale). Archives of Geology, General Dept. Geology and Minerals of Viet Nam, Hanoi. Nguyen Xuan Tung, Tran Van Tri, 1992. Geological formations and geodynamics of Viet Nam. Science & Technology Publisher, Hanoi. Pham Duc Luong, Dang Tran Huyen, Nguyen Dinh Huu, Nguyen Duc Phong, Nguyen Thi Bich Thuy, 2010. Zircon U-Pb ages of volcanic rocks in the Tu Le Basin. Dia Chat (Journal of Geology), 320/9-10/2010 in Vietnamese with English abstract. Phan Cu Tien (Editor), 1989. Geology of Campuchia, Laos and Viet Nam 1:1,000,000 scale. General Dept. Geology and Minerals of Viet Nam, Hanoi. Phan Cu Tien (Editor), 1977. Explanations of geological maps of northwest Viet Nam: the Song Da sheet of 1:200,000. Science and Technology Publisher, Hanoi. Royden, L.H., Burchfiel, B.C., van der Hilst, R.D., 2008. The Geological evolution of the Tibetan Plateau. Science 321(5892), 1054-1058. Sun, S.-S., McDonough, W.F., 1995. The composition of the Earth. Chemical Geology 120, 223-253. Tapponnier, P., Lacassin, R., Leloup, P.H., Schärer, U., Zhong, D.L., Wu, H.W., Liu, X.H., Ji, S.C., Zhang, L.S., Zhong, J.Y., 1990. The Ailao Shan/Red River metamorphic belt: Tertiary left-lateral shear between Indochina and South China. Nature 343, 431-437. Tapponnier, P., Molnar, P., 1977. Active faulting and tectonics of China. Journal of Geophysical Research 82, 2905-2930. Tapponnier, P., Peltzer, G., Armijo, R., Le Dain, A.Y., Cobbold, P., 1982. Propagating extrusion tectonics in Asia: New insights from simple experiments with plasticine. Geology 10, 611-616. Tapponnier, P., Xu, Z.-Q., Roger, F., Meyer, B., Arnaud, N., Wittlinger, G., Yang, J.-S., 2001. Oblique stepwise rise of growth of the Tibet Plateau. Science 294, 1671-1677. Taylor, S.R., McLennan, S.M., 1981. The composition and evolution of the continental crust: rare earth element evidence from sedimentary rocks. Philosophical Transactions of the Royal Society of London 301, 381-399. Tran Duc Luong, Nguyen Xuan Bao, 1988. Geological map of Viet Nam, 1:500,000 scale. General Dept. Mines and Geology, Hanoi, Viet Nam. Tran Trong Hoa, 1996. Mesozoic - Cenozoic magmatism in northwest Viet Nam and Truong Son: geochemical compositions, magma generation and mineral resource potential. Journal of Earth Sciences, 18, 2018-227. Tran Trong Hoa, Izokh, A.E., Polyakov, G.V., Borisenko, A.S., Tran Tuan Anh, Balyakin, P.A., Ngo Thi Phuong, Rudnev, S.N., Vu Van Van, Bui An Nien, 2008. Permian - Triassic magmatic activity and mineral resources in northwest Viet Nam and the connection to Emeishan mantle plume. Journal of Geology and Geophysics, 49, 480-491 (in Russian). Tran Tuan Anh, Tran Trong Hoa, Lan, C-Y., Chung, S-L, Lo, C-H., Wang, P-L., Mertzman, S. 2004. Mesozoic bimodal alkaline magmatism in Tu Le basin, North Vietnam: Constraints from geochemical and isotopic significances. J. Geology, Ha Noi, Series B(24), 1-9. Tran Tuan Anh, Tran Trong Hoa, Pham Thi Dung, 2002. Granites in the Ye Yen Sun complex and their significances in tectonic interpretation of the early Cenozoic stage in West Bac Bo. Journal of Geology B(19-20), 43-53. Tran Van Tri (Editor), 1977. Geology of Viet Nam, northern part. Science and Technology Publisher, Hanoi. Tran Van Tri, Nguyen Xuan Tung, 1979. Geotectonic evolution of Northern Vietnam. XIV Pacific Sci. Congr. Com. B, sect. II, 48-49, Khabarovsk. Tran Van Tri (Editor), 1979. Geology of Vietnam (North Part). General Department of Geology, Research Institute of Geology and Mineral Resources. Tran Van Tri, Tran Trong Hoa, 2011. Late Paleozoic-Mesozoic Song Da - Tu Le intracontinental rift system. Geology and Natural Resources, Science and Technology Publisher, Hanoi, 425-431. Vu Khuc, Bui Phu My, 1989. Geology of Viet Nam. Vol I. Stratigraphy). General Dept. Mines and Geology of Viet Nam, Hanoi, 378 (in Vietnamese). Vu Khuc, Tran Trong Hoa, 2007. Current study status of the volcano-sedimentary Tu Le basin and remaining problems. Journal of Sciences of the Earth, 29(4), 296-300 9 (in Vietnamese). White, W.M., Hofmann, A.W., Puchelt, H., 1987. Isotope geochemistry of Pacific mid-ocean ridge basalt. Journal of Geophysical Research 92(B6), 4881-4893. Xu, J.-F., Castillo, P.R., 2004. Geochemical and Nd- Pb isotopic characteristics of the Tethyan asthenosphere: implications for the origin of the Indian Ocean mantle domain. Tectonophysics 393, 9-27. Xu, X.S., Griffin, W.L., O’Reilly, S.Y., Pearson, N.J., Geng, H.Y., Zheng, J.P., 2008. Re-Os isotopes of sulfides in mantle xenoliths from eastern China: progressive modification of lithospheric mantle. Lithos 102, 43-64. Xu, Y.-G., Chung, S.L., Jahn, B.M., Wu, G.Y., 2001. Petrologic and geochemical constraints on the petrogenesis of Permian-Triassic Emeishan flood basalts in southwestern China. Lithos 58, 145-168. Yang, Y., Liu, M., 2009. Crustal thickening and lateral extrusion during the Indo-Asian collision: A 3D viscous flow model. Tectonophysics 465, 128-135.